Military healthcare ethics - Practicing healthcare ethically in a military setting - Blessing Asemota-Akpeji (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Military healthcare operates differently from medical healthcare. Even though they provide the same services, treating sick and wounded patients, military healthcare is governed by different ethics. To practice as a Military healthcare professional, crucial skills are needed. Military healthcare professionals are bound by medical ethics of saving lives first and being loyal to their country on the war front. Even though they are not involved in fighting on the war front, they make equally essential decisions regarding who gets to be treated and even save the enemy. This article expands on some of the crucial needs and requirements necessary to practice as a military healthcare professional and how different this is from civilian medical practice.